The Use of Particle Swarm Algorithm to Solve Queuing Models with Practical Application - رضا, صباح منفي; ابراهيم, انسام علاوي (Journal of Economics and Administrative Sciences, 2017)
This paper includes the application of Queuing theory with of Particle swarm algorithm or is called (Intelligence swarm) to solve the problem of The queues and developed for General commission for taxes /branch Karkh center in the service stage of the Department of calculators composed of six  employees , and it was chosen queuing model is a single-service channel  M / M / 1 according to the nature of the circuit work mentioned above and it will be divided according to the letters system for each employee, and  it was composed of data collection times (arrival time , service time, departure time) In minutes , Where it was data Test the obtained them found it distributed statistical distribution commensurate with the nature of the data and when tested were found to be distributed the distribution of arrival (Discrete Uniform distribution) and the distribution service (Exponential distribution ) , and it was finding performance measures (the service provided) in the system ( Ls , Lq , Ws , Wq ), and the problem is resolved to the research using software MATLAB R2013a Version : 8.1  and it get the required results, and This paper aims Solve the problem of The queues in General commission for taxes / branch Karkh center and reduce the customer waiting times and improving the efficiency of the service provided.